Charakterystyka sektorowego programu operacyjnego realizowanego przez FAPA i urzędy marszałkowskie - Wojtasik, Bolesław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The aim of the research was to analyze the role of FAPA and marshal offices in realization of the SPO - agriculture actions. There were taken three main tasks by FAPA, mainly concentrated in broadening agricultural knowledge, provisioning of advisory services and preparation of the rural society to initiate community initiatives (Leader+ Programme). An another role of the process, which was due to the marshal offices as local government units, was to obligate to proper usage of water re-sources and preservation of cultural heritage (county restoration). (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 42-48